Determinant Of MSMEs Actors' Interest in Applying for Halal Certification (Towards Halal Mandatory 2024) - Effasa, Ahmad Saifurriza; Rochmayanti, Dewi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In UUD No.33 of 2014, it is explained that the halal certification decision "halal certification must be present on all products", in its implementation or reality, there are still many products that have not received halal certification. The direction of this research is to examine the impact of religion on halal certification procedures partially and simultaneously, and halal certification regulations on interest in halal certification among MSMEs in Bojonegoro. Based on 168 questionnaires distributed to the audience, by applying proportional stratified random sampling techniques and studied using a multiple linear regression model, research results were obtained which showed that religiosity, halal certification procedures, and certification regulations simultaneously influence the interest in halal certification among MSMEs actors in Bojonegoro. Partially, the variables of religiosity, halal certification procedures, and certification regulations have a positive and significant influence on the interest in Halal Certification among MSMEs in the Bojonegoro area.